Implementation effectiveness of Islamic microfinance program in Selangor - Hamdan, Hamdino; Othman, Pazim @ Fadzim; Abdol Ghani, Mohd Reza (Kolej Polytech MARA, 2011)
Islamic Micofinance Program (IMP) through the utilization of zakat fund has been a significant source of capital for entrepreneurship activities among the poor Muslim's family in Malaysia. Eversince New Economic Plan (NEP) was introduced in 1971, the Malaysian government has realized the important of IMP in supporting the micro-enterprises activities for the purpose of poverty eradication strategy. 'Asnaf Entrepreneurship Development Program' conducted by Lembaga Zakat Selangor (LZS) is among the pioneers and the most established IMP's being introduced in Malaysia. However there may be doubts as to whether this program has achieve its objectives of increasing the socio-economic level of the poor. Therefore the focus of this study is to evaluate the implementation effectiveness of 'asnaf entrepreneur development' in increasing the participants income for the purpose of poverty eradication, through the entrepreneurial concept by conducting microenterprise. The results show that the program's process and procedures, officer's qualifications, attitudes and experiences affected the participants' business revenue.